Perilaku Tata Kelola Bahasa pada Generasi Z Terhadap Bahasa Indonesia Sebagai Bahasa Nasional - Kartika, Amalia; Trinanda, Reva Elgi; Pangesti, Rizky; Nurhidayatussholikhah, Siti; Anhar, Anhar; Ladislapenny, Sabilla Bias (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the use of Indonesian among Generation Z and its relevance to the function of the national language in the digital age. As a generation of digital natives, Generation Z presents both challenges and opportunities in efforts to preserve Indonesian. This study uses a phenomenological qualitative approach with data collection techniques through in-depth interviews, observation of linguistic activities on social media, and analysis of digital documents. The data were analysed thematically through a process of reduction, categorisation, and meaning extraction to identify distinctive patterns of language use. The results show that Generation Z's language practices are characterised by linguistic creativity, code-mixing between Indonesian and foreign languages, and the emergence of new forms of digital expression. A gap was also found between normative language policies and the more dynamic and flexible language practices of Generation Z. The implications of this research emphasise the importance of developing adaptive, participatory, and digitally-based language policy and development models so that Indonesian remains relevant and competitive amid global disruption